Antitumor polycyclic acridines. 7. Synthesis and biological properties of DNA affinic tetra- and pentacyclic acridines - Stanslas, Johnson; Hagan, Damien J.; Ellis, Michael J.; Turner, Claire; Carmichael, James; Ward, Wynne; Hammonds, Timothy R.; Stevens, Malcolm F. G. (American Chemical Society, 2000)
New synthetic routes to a series of tetra- and pentacyclic acridines related in structure to marine natural products are reported. The novel water-soluble agent dihydroindolizino[7,6,5-kl]acridinium chloride 14 has inhibitory activity in a panel of non-small-cell lung and breast tumor cell lines exceeding that of m-AMSA. The salt inhibited the release of minicircle products of kDNA confirming that disorganization of topoisomerase II partly underlies the activity of the compound. COMPARE analysis of the NCI mean graph profile of compound 14 at the GI50 level corroborates this conclusion with Pearson correlation coefficients (> 0.6) to clinical agents of the topoisomerase II class: however, this correlation was not seen at the LC50 level. The inhibitory action of 14 on Saccharomyces cerevisiae transfected with human topoisomerase II isoforms showed a 3-fold selectivity against the IIα isoform over the IIβ isoform. Unlike m-AMSA, 14 is not susceptible to P-glycoprotein-mediated drug efflux and retains activity in lung cells with derived resistance to the topoisomerase II inhibitor etoposide.